Strategies for understanding archetypes and the collective unconscious of an organization - Smetana, Judy B., author; Gilley, Jerry W., advisor; Banning, James H., committee member; Folkestad, James, committee member; Morgan, George A., committee member (Colorado State University. Libraries, 2006)
Understanding archetypes as basic components of the collective unconscious and understanding archetypes within the context of organizational culture is an important aspect of this study. Considering organizational archetypes in the context of organizational culture and testing for archetypes in organizations to gain an understanding of the archetypal story might aid in a better perception of the complexity of organizational culture. Using both an organizational ethnography and the OTCI instrument to study the collective unconscious and archetypes could prove to further our understanding of these constructs. The significance of the study lies therein that the collective unconscious along with the archetypes poses an interesting phenomena in the investigation of organizational culture. By understanding the archetypes of an organization we may begin to understand the factors, which drive the organizational culture. The intent of this mixed design study was to explore the similarities and differences generated by two methods of inquiry, namely an organizational ethnography and the OTCI instrument. Both of these methods were testing for archetypes in an organization. The results showed that although there are some relatively large differences between the OTCI and Interview rankings, there was substantial agreement on most of the archetypes. This agreement is reflected by the significant, large effect size correlations discussed in the study. the archetypes. This agreement is reflected by the significant, large effect size correlations discussed in the study. The researcher believes if an individual's values, beliefs, and strengths are connected, universally, as Jung (1959) suggested, then this connection, namely the archetype can help us assess an organization and its culture. Archetypes are then a statement of what an organization is actually living. And, this is exactly what the archetypal findings and the story of EPC (the organization) represent. They represent a creation and re-creation of what participants have lived and are living at EPC. In this case, testing for archetypes and understanding the archetypal story could prove to give us a deeper sense and structure of our organizations and their cultures.
Keywords: cultural anthropology